Identification and Characterization of Circulating MicroRNAs as Novel Biomarkers in Dogs With Heart Diseases - Ro, Woong-Bin; Kang, Min-Hee; Song, Doo-Won; Kim, Heyong-Seok; Lee, Ga-Won; Park, Hee-Myung (Frontiers in Veterinary Science, 2021)
Background: Previous studies in humans have confirmed dysregulations of circulating microRNAs (miRNAs) in patients with various cardiovascular diseases. However, studies on circulating miRNAs in dogs with various heart diseases are limited in number. This study aimed to identify significantly dysregulated circulating miRNAs and characterize them as novel biomarkers in dogs with heart diseases. Materials and Methods: Circulating levels of eleven miRNAs were investigated in serum samples of 82 dogs (72 with heart diseases and 10 healthy dogs) using quantitative reverse transcription-polymerase chain reaction. The results were correlated to clinical data including echocardiographic results and N-terminal pro B-type natriuretic peptide (NT-proBNP) levels. Results: Up-regulation of cfa-miR-130b was observed in dogs with myxomatous mitral valve degeneration (MMVD) stage B, patent ductus arteriosus, and pulmonic stenosis. In dogs with MMVD stage B, cfa-miR-130b was up-regulated and correlated with clinical indices. In receiver operating characteristic (ROC) analysis, cfa-miR-130b accurately distinguished dogs with diseases from healthy dogs. We also observed that cfa-miR-375 and cfa-let-7b were up-regulated in dogs with concentric cardiac hypertrophy. The cfa-miR-375 was correlated with concentric hypertrophy indices and was an accurate indicator of concentric hypertrophy in ROC analysis. Conclusions: The miRNAs identified in this study may be used as novel biomarkers and possible candidates for therapeutic targets in various canine heart diseases.